KORELASI KEPRIBADIAN DENGAN ALTRUISME PERAWAT RUMAH SAKIT DI MALANG - Ike Prafita Sari; Ika Suhartanti; Fitria Wahyu Ariyanti; Fitri Yuliati (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
Altruism owned by nurses could increase patient motivation to recover soon. On the other hand, the nurses with a low altruism level could bring bad impression for patient, so the patient motivation to recover was decreased. One of factors that could affect altruism was personality. Personality was a whole way of individual communicates with other individuals. One of personality theories that was often used was big five personality. The aim of this research was to analyze the relation between big five personality and altruism of hospital nurses in Malang. This research used cross sectional design and simple random sampling technique. The total samples in this research were about 80 nurses. Moreover, this research was conducted in February, 2022. The research result referred that the category of positive behavior in nurse altruism variable has value of 53,75%, while the category of positive behavior in big five personality variable has value of 71,25%. Based on the Rank Spearman’s statistic test calculation, it showed value of α = 0,005, with correlation coefficient of 0,314. Therefore, it could refer a relation between big five personality and nurse altruism, or H1 was approved. This result was in line with various factors that could affect altruism such as presence of other individuals, environmental condition, time pressure, personality factor, mood, distress, empathy, and help for the loved person. This research expected that the nurses always have personality development, so they could provide a comprehensive nursing care along with provision of actual science.